Flaubert et l’image légendaire / légendée - Sabine Narr (Flaubert: Revue Critique et Génétique)
In many ways legends are at the heart of Flaubert’s work. Indeed, his writings show a subtle reception of the hagiography which focuses on the imaginary potential of legends, in their esthetic and intermedial dimension. Studying the legend-form allows us to reveal the complex relationship between the Flaubertian text and visual arts. This article shows, such as in Madame Bovary and Un cœur simple, the mutual clarifications between the text and the legendary image/caption. Rereading these two texts illustrates how a creative reception of the medieval form operates, a reception which greatly takes into account the new optical machines emerging in the 19th century.